Representasi Nilai Religi dalam Media Film Horor: Studi Persepsi Penonton pada Film Thaghut - Ummah, Syadathul (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2024)
The rise of horror movies that present religious themes to evoke scary things makes people more afraid to worship. The movie Kiblat is one of the movies that was criticized because there were scenes and posters that were considered insulting to Islam, so after various criticisms the movie was transformed into Thaghut and began to change posters and cut some scenes that were considered inappropriate. Researchers are interested in seeing the perceptions of audiences (Thaghut movie viewers) about the pros and cons whether audiences still have confidence in the existence of media idealism so that they still choose to watch the film. This research was analyzed using the SEM PLS technique which was distributed to 348 respondents with a total of 16 statement items. So that it gives the results that there is an influence of media idealism on audience perceptions with a total percentage of 68% so that the audience has confidence in the media to be able to meet the needs of the audience and believe that there are no elements of religious insults in this film, while the remaining 32% is influenced by other factors. This article is written for the audience's understanding of the importance of being selective in absorbing media information so that they are not easily led by opinions that are not yet known in fact.